Crete, Thera, and the Problems with Minoanization: An Examination of Cultural Contact in the Bronze Age Aegean - Bigioni, Emily M. (Tufts Archival Research Center, 2023)
Sometimes called the “Pompeii of the Bronze Age” or the “Pompeii of the Ancient Aegean”, the site of Akrotiri on Thera is a startlingly well preserved Late Bronze Age town first uncovered in the 1960’s from under feet of volcanic tephra which was deposited after a catastrophic eruption destroyed the island. It predates its Roman counterpart by over one and a half thousand years. Long treated as a Minoan colony, what the archaeological evidence recovered from Thera actually shows is a Cycladic island town whose local character endured even as Minoan influence grew. This paper examines the ways in which the myth of a Minoan thalassocracy developed under Sir Arthur Evans, and how that myth has molded subsequent understanding of the presence of Minoan artifacts and other aspects of Minoan material culture outside of Crete. There is no deciphered written evidence from the site of Akrotiri, making understanding its history difficult. In light of the recent trend to reexamine Minoanization as a phenomenon and to consider the islands’ own actions as a source of their Minoanization, this paper analyzes material cultural evidence to provide a perspective of Akrotiri as the location of a bustling trading town which, coming into frequent trade contact with Crete, began to embody many aspects of Minoan Cretan material culture while still maintaining local character.; Thesis (B.A.)--Tufts University, 2023.; Submitted to the Dept. of History.